Situated language and learning : a critique of traditional schooling - Gee, James Paul (Literacies., 2004)
Tackles the big ideas about language, literacy and learning. Why do poor and minority students under-perform in school? Do computer games help or hinder learning? What can new research in psychology teach our educational policy makers?